Upon Repeated Reflection: Consequences of Frequent Exposure to the Cognitive Reflection Test for Mechanical Turk Participants - Woike, Jan K. (Frontiers in Psychology, 2019)
Participants from public participant panels, such as Amazon Mechanical Turk, are shared across many labs and participate in many studies during their panel tenure. Here, I demonstrate direct and indirect downstream consequences of frequent exposure in three studies (N(1-3)=3,660), focusing on the cognitive reflection test (CRT), one of the most frequently used cognitive measures in online research. Study 1 explored several variants of the signature ball-and-bat item in samples recruited from Mechanical Turk. Panel tenure was shown to impact responses to both the original and merely similar items. Solution rates were not found to be higher than in a commercial online panel with less exposure to the CRT (Qualtrics panels, n=1,238). In Study 2, an alternative test with transformed numeric values showed higher correlations with validation measures than the original test. Finally, Study 3 investigated sources of item familiarity and measured performance on novel lure items.